Effect of admission time on provision of acute stroke treatment at stroke units and stroke centers—An analysis of the Swiss Stroke Registry. (June 2022) - Altersberger, Valerian L; Wright, Patrick R; Schaedelin, Sabine A; De Marchis, Gian Marco; Gensicke, Henrik; Engelter, Stefan T; Psychogios, Marios; Kahles, Timo; Goeldlin, Martina; Meinel, Thomas R; Mordasini, Pasquale; Kaesmacher, Johannes; et al.
Introduction: Rapid treatment of acute ischemic stroke (AIS) depends on sufficient staffing which differs between Stroke Centers and Stroke Units in Switzerland. We studied the effect of admission time on performance measures of AIS treatment and related temporal trends over time. Patients and methods: We compared treatment rates, door-to-image-time, door-to-needle-time, and door-to-groin-puncture-time in stroke patients admitted during office hours (Monday–Friday 8:00–17:59) and non-office hours at all certified Stroke Centers and Stroke Units in Switzerland, as well as secular trends thereof between 2014 and 2019, using data from the Swiss Stroke Registry. Secondary outcomes were modified Rankin Scale and mortality at 3 months. Results: Data were eligible for analysis in 31, 788 (90.2%) of 35, 261 patients. Treatment rates for IVT/EVT were higher during non-office hours compared with office hours in Stroke Centers (40.8 vs 36.5%) and Stroke Units (21.8 vs 18.5%). Door-to-image-time and door-to-needle-time increased significantly during non-office hours. Median (IQR) door-to-groin-puncture-time at Stroke Centers was longer during non-office hours compared to office hours (84 (59–116) vs 95 (66–130) minutes). Admission during non-office hours was independently associated with worse functional outcome (1.11 [95%CI: 1.04–1.18]) and increased mortality (1.13 [95%CI: 1.01–1.27]). From 2014 to 2019, median door-to-groin-puncture-time improved and the treatment rate for wake-up strokes increased. Discussion and Conclusion: Despite differences in staffing, patient admission during non-office hours delayed IVT to a similar, modest degree at Stroke Centers and Stroke Units. A larger delay of EVT was observed during non-office hours, but Stroke Centers sped up delivery of EVT over time. Patients admitted during non-office hours had worse functional outcomes, which was not explained by treatment delays. Graphical abstract